2018
DOI: 10.1021/acs.nanolett.8b02687
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Single Photons from Discrete Quantum Emitters in WSe2 to Lithographically Defined Plasmonic Slot Waveguides

Abstract: We report the observation of the generation and routing of single plasmons generated by localized excitons in a WSe monolayer flake exfoliated onto lithographically defined Au-plasmonic waveguides. Statistical analysis of the position of different quantum emitters shows that they are (3.3 ± 0.7) times more likely to form close to the edges of the plasmonic waveguides. By characterizing individual emitters, we confirm their single-photon character via the observation of antibunching in the signal ( g(0) = 0.42)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 46 publications
3
54
0
Order By: Relevance
“…The routing of single photons was successfully demonstrated in plasmonic [102,103] as well as dielectric waveguide [104][105][106]. Statistical analysis of the position of different quantum emitters coupled to plasmonic waveguides showed that they are more likely to form close to the edges of the waveguides [103] with Purcell factor up to 15 ± 3, thus negating the need for pick and place. The coupling of single localized defects in a WSe 2 monolayer was shown to self-align to the surface plasmon mode of a silver nanowire, thus presenting an average coupling efficiency of 26 ± 11%.…”
Section: Integration With Photonic Structuresmentioning
confidence: 99%
“…The routing of single photons was successfully demonstrated in plasmonic [102,103] as well as dielectric waveguide [104][105][106]. Statistical analysis of the position of different quantum emitters coupled to plasmonic waveguides showed that they are more likely to form close to the edges of the waveguides [103] with Purcell factor up to 15 ± 3, thus negating the need for pick and place. The coupling of single localized defects in a WSe 2 monolayer was shown to self-align to the surface plasmon mode of a silver nanowire, thus presenting an average coupling efficiency of 26 ± 11%.…”
Section: Integration With Photonic Structuresmentioning
confidence: 99%
“…Beyond the response of mobile excitons, also quantum dot-like emission from localized excitons was recently demonstrated in WSe 2 1014 , GaSe 15 , MoSe 2 16 , and WS 2 17 and the nature of the potential, which localizes the excitons is still not fully understood. The origin of such quantum emitters was hitherto considered to be caused by uncontrolled strain potentials that locally reduce the band gap, thus, funneling the recombination of excitons via a discrete recombination center 1720 . However, strain potentials are challenging to control, which limits the applicability of such quantum emitters for a prospective integration into quantum photonic circuits 2025 .…”
Section: Introductionmentioning
confidence: 99%
“…14 This opens opportunities for coupling and/or energy routing between SPE sites in 2D semiconductors for potential applications such as on-chip quantum light sources. [15][16][17] In addition, metal nanostructures can lead to enhanced Purcell factors resulting in increased single-photon emission rates. 9,18 As such, it is natural to imagine interfacing 2D semiconductor SPEs with metals to advance quantum and optical processing technology.…”
Section: Introductionmentioning
confidence: 99%